(untitled) (Международный научный журнал «Инженер», 2026)
The results of a study on the influence of serpentinite on the properties of ceramovermiculite are presented. The introduction of a natural magnesium-containing material into the mixture increases the strength of the samples while decreasing shrinkage and density. The combined addition of serpentinite, coal (as a combustible additive), and nepheline made it possible to obtain ceramovermiculite materials with high thermophysical properties